COST FUNCTION BASED FORWARD NODE SELECTION TOWARDS ENERGY OPTIMIZATION FOR INTERNET OF MEDICAL THINGS - Rahat Ali Khan; Shahzad Memon (Spectrum of Engineering Sciences, 2025)
Internet of Medical Things is an important field of research which focusses towards the betterment of human health. It comprises of tiny sized sensors that can record changes in human physiological parameters. These sensors have limited source of battery power due to their size. As the transmission is wireless in nature so there is reduction in the strength of transmitted signal due to attenuation. This attenuation is due to path loss. In this paper a cost function based technique is proposed to be used in order to minimize the signal attenuations.